2007
DOI: 10.1161/circulationaha.107.182615
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Care in the Elderly, Part I

Abstract: Background— Age is an important determinant of outcomes for patients with acute coronary syndromes (ACS); however, community practice reveals a disproportionately lower use of cardiovascular medications and invasive treatment even among elderly patients with ACS who would stand to benefit. Reasons include limited trial data to guide the care of older adults and uncertainty about benefits and risks, particularly with newer medications or invasive treatments and in the setting of advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
196
3
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 680 publications
(223 citation statements)
references
References 133 publications
(107 reference statements)
11
196
3
13
Order By: Relevance
“…Prior studies demonstrated suboptimal adherence to statins among older patients with MI, and low medication adherence was associated with a higher risk of major cardiovascular events 17, 18. The high observed death rate in older patients may reflect the influence of multiple comorbidities and frailty on post‐MI recovery 1. Our study underscores the large comorbidity burden among older MI patients; 77% had hypertension, 35% had diabetes mellitus, 17% had renal insufficiency, and 13% had prior stroke.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Prior studies demonstrated suboptimal adherence to statins among older patients with MI, and low medication adherence was associated with a higher risk of major cardiovascular events 17, 18. The high observed death rate in older patients may reflect the influence of multiple comorbidities and frailty on post‐MI recovery 1. Our study underscores the large comorbidity burden among older MI patients; 77% had hypertension, 35% had diabetes mellitus, 17% had renal insufficiency, and 13% had prior stroke.…”
Section: Discussionmentioning
confidence: 58%
“…Novel medication approaches to secondary prevention may be of particular interest to older patients with MI. Furthermore, older patients with MI are often excluded or underrepresented in clinical trials 1. The high observed mortality underscores the need for older patients with MI to be represented in these trials, and also that trials involving this high‐risk group can be informative with relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Although elderly patients were more likely to have worse clinical profile; they were less likely to receive guideline-recommended medical and interventional therapies. Previous studies 13,19,23e25 reported similar age-dependent results.…”
Section: Hospital Management and Outcomesmentioning
confidence: 99%